2017
DOI: 10.1177/1077801217708887
|View full text |Cite
|
Sign up to set email alerts
|

The Psychology of the Politics of Rape: Political Ideology, Moral Foundations, and Attitudes Toward Rape

Abstract: Previous research has found that conservatives and liberals emphasize different moral foundations. The purpose of these two studies was to investigate whether moral foundations mediate the relationship between political ideology and attitudes toward rape among U.S. college students. In Study 1, moral foundations fully mediated the relationship between political ideology and rape myth acceptance. Study 2 generally replicated the results of Study 1, with binding foundations demonstrating the most consistent medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…Regarding the link between rape myths and moral foundations, Barnett and Hilz () found that rape myth acceptance is associated positively with binding foundations and negatively with individualizing foundations. However, they did not study moral foundations in relation to victim blaming in specific rape cases.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the link between rape myths and moral foundations, Barnett and Hilz () found that rape myth acceptance is associated positively with binding foundations and negatively with individualizing foundations. However, they did not study moral foundations in relation to victim blaming in specific rape cases.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in Study 1, rape myth acceptance and system justification are positively correlated with belief in biological origin of gender differences thus we decided to control for it in Study 2. Taking into account the correlation between rape myth acceptance and conservative world view (Barnett & Hilz, 2017;Giovannelli & Jackson, 2013;Hantzi et al, 2015;Łyś et al, 2021) we decided to also control for political views. Given the evidence for the influence of the emotional state on acquisition of information (e.g., Imbir, 2016), as well as the evidence for the link between the mood and blame attribution (Goldenberg & Forgas, 2012), we decided to include mood as a covariate.…”
Section: Study 2: Exposure To Essentialist and Anti-essentialist Content And Beliefs On Sexual Violencementioning
confidence: 99%
“…First, insofar as morality is a potentially powerful constraint on sex buying, the theoretical models described in prior sex buying research may be incomplete. Second, research documents that moral beliefs differ across social and demographic groups (Graham et al, 2009(Graham et al, , 2011Miles, 2014), and are associated with attitudes regarding sexual permissiveness (Haidt & Hersh, 2001), rape myth acceptance (Barnett & Hilz, 2018;Gable et al, 2017), sexism (Vecina & Piñuela, 2017), and adherence to traditional gender roles (Graham et al, 2011). Thus, empirically, prior research focusing solely on demographic or genderbased explanations for sex buying may suffer from omitted variable bias and either overstate or understate the relationships between sex buying and other theoretically relevant variables.…”
Section: Why Men Buy Sexmentioning
confidence: 99%